Measuring ministerial stability at the beginning of the Argentine state (1898–1930) - Abal Medina, Juan Manuel; Eberhardt, María Laura; Ariza, Andrea (Estado, Gobierno y Gestión Pública, 2021)
This article reviews and analyzes the composition and stability of the cabinet of ministers of Argentine presidents since the constitutional reform of 1898 until the country’s first military coup in 1930. The first objective is to account for the ministers who were appointed in the various departments and their permanence in them. The source to be used is the Book of the Members of the Government of the Argentine Nation, belonging to the General Office of the Nation. Second, the stability / instability of the cabinets will be analyzed, measured using a specific tool proposed here, the Cabinet Stability Index, which seeks to become a useful instrument for future analyzes of other periods and / or other presidential regimes. Finally, reflections will be made about the results obtained, under a political perspective that in turn articulates the historical consideration of the time.